RELEVANSI KEMAMPUAN PRASYARAT DALAM PENGUASAAN KONSEP MAHASISWA - Widyawati, Eka (Almeera Education, 2025)
The mathematics material that has been taught to students will be a prerequisite for the next material. So if the previous material has not been fully mastered by students, it will affect the mastery of concepts in the next material. In the Introduction to Basic Mathematics course presented in semester I in the mathematics education department, it contains basic materials such as sets, functions, and logic that have been studied in high school. So the prerequisite material that must be mastered by students is the material that has been obtained in high school. What is needed in learning mathematics is to understand the concepts in a structured manner starting from basic concepts to moving on to more advanced material. This study aims to determine the relevance of prerequisite abilities to students' mastery of concepts. The research method used is ex post facto. The subjects of this study were 30 first semester students at Borneo Tarakan University. The instruments used were prerequisite ability tests and concept mastery tests in the Introduction to Basic Mathematics course. The analysis used was Pearson correlation test data analysis using SPSS 30 for windows. Based on the results of the analysis, a correlation coefficient value of 0.796 was obtained so that there was a relationship and significance between the two variables, where the relationship between the two variables was in a strong relationship